SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PENERIMA KIP KULIAH STMIK SYAIKH ZAINUDDIN NW - Zulkarnaen Zulkarnaen; Hizbullah Hizbullah; Lalu Puji Indra Kharisma (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2026)
KIP Kuliah is a government tuition assistance program for High School graduates who have good academic potential but face economic constraints. STMIK Syaikh Zainuddin NW Anjani faces challenges in the KIP Kuliah recipient selection process due to the large number of applicants and diverse assessment criteria, which risks subjectivity and inaccurate targeting. This study aims to build a Decision Support System (DSS) that can assist the campus in determining KIP Kuliah recipients objectively and efficiently. The method used in this system is the Simple Multi-Attribute Rating Technique (SMART) method, which works by assigning weights to each criterion and calculating the final value based on normalization. The criteria used include parental income, academic/non-academic achievements, home ownership status, parental dependents, and other economic conditions. The result of this research is a web-based application capable of processing applicant data and generating a ranking of potential KIP Kuliah recipients according to predetermined criteria weights. System testing shows that the SMART method is effective in providing transparent and accurate decision recommendations for the management of STMIK Syaikh Zainuddin NW.